Corporate Responsibility and Intimate Partner Violence:A Management Perspective on Supporting Women in the Workplace - Garima Juneja, Saurabh Chaturvedi (Journal of Informatics Education and Research, 2025)
Intimate partner violence (IPV) represents one of the most pervasive and devastating social issues affecting modern workplaces, with far-reaching implications for employee wellbeing, organizational productivity, and corporate responsibility. This research paper examines the critical role of corporate responsibility in addressing intimate partner violence through a management perspective, with particular focus on supporting women employees who experience abuse. The study explores how organizations can integrate IPV support into their corporate social responsibility frameworks while developing effective management strategies to create safer, more supportive workplace environments. Current statistics reveal the alarming scope of this issue: approximately 24% of women and 11% of men who are victims of intimate partner violence miss at least five days of work per month, while 74% of employed domestic violence victims are targeted during work hours. These figures underscore the urgent need for comprehensive corporate responses that extend beyond traditional employee assistance programs to encompass holistic support systems grounded in organizational responsibility and ethical management practices.